Proposed new interior design scheme of Ramly Burger Cafe for Ramly Food Processing at 01,01-1,01-2, Jalan Marina, Marina Island Kilometer 1, Teluk Muroh Lumut,Perak / Fasihah Azizan - Azizan, Fasihah (Faculty of Architecture, Planning and Surveying, 2011)
Final project report is something very important in the diploma level. This is the manifestation of an individual knowledge about all aspect of the process that has been learning from the basic to the higher level. This is because in order to ensure students can carry out interesting presentation in interior design. This final project report is about to Proposed New Interior Design Scheme of Ramly Burger Cafe for Ramly Food Processing Sdn.Bhd at D1, D1-1, D1-2, Jalan Marina, Marina Island Kilometer 1, Teluk Muroh 32000, Lumut Perak. The aim of this project for proposed a new image to it interior and to appeal the corporate image. Besides, to create a new design scheme of space requirement for the cafe and new branding for new fast food franchise restaurant. In addition, the purpose of this project was created to develop more products for Ramly business. The products are very well-known in the community indeed in Malaysia, Brunei and Singapore. The factory has achieved the highest level of quality in processing the burger, nugget and also the sausages. The most important thing this label has been recognized as Halal product for food selection especially muslim. To complete the requirement of this project, interview, research and observation is being doing to make sure the data are required and will be analyzed in the design process. Thus, the requirements are depend on the location that has to be strategic, size, image, circulation and the character of the cafe. So the customer will feels more relax, friendly atmosphere, cleanliness, comfort, and convenience.